1991
DOI: 10.1161/01.hyp.17.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Reduced calcium sensitivity of dihydropyridine binding to calcium channels in spontaneously hypertensive rats.

Abstract: To explore the role of calcium channels in hypertension, dihydropyridine ([ 3 H]PN200-110) binding to heart, brain, and skeletal muscle microsomes of 4-, 8-and 15-week-old spontaneously hypertensive rats (SHR) and Wistar-Kyoto (WKY) rats was measured. At a constant Ca 2+ ion concentration (pCa 3.0), maximal binding (B^J of dihydropyridine binding to heart and brain microsomes was significantly enhanced in 8-and 15-week-old SHR compared with WKY rats (/?<0.01), whereas this phenomenon was not observed in 4-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
3
1
0
Order By: Relevance
“…Ionomycin also induced a greater increase in [Ca 2+ ]i in T‐cells of diabetic rats compared with those of control rats. Our findings can be supported by the observations of Ebata et al (52), who have reported an increased density of calcium channels in diabetic rats. Similarly, ionomycin‐induced calcium increase was higher in T‐cells of obese pups than in those of control animals.…”
Section: Discussionsupporting
confidence: 93%
“…Ionomycin also induced a greater increase in [Ca 2+ ]i in T‐cells of diabetic rats compared with those of control rats. Our findings can be supported by the observations of Ebata et al (52), who have reported an increased density of calcium channels in diabetic rats. Similarly, ionomycin‐induced calcium increase was higher in T‐cells of obese pups than in those of control animals.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, we hypothesize that the plasma membranes of T cells from SHR may have different composition than those of WKY rats. This is supported by the findings of Ebata et al (1999) who reported an increased density of L-type calcium channels in heart and brain of SHR.…”
Section: Discussionsupporting
confidence: 80%
“…It is interesting that human and experimental hypertensive states other than pre‐eclampsia have also been associated to an increased density of calcium channels 41 . Similarly to what we have found in pre‐eclampsia, studies using labelled nitrendipine and PN 200 110 42 also reported an increased density and affinity of calcium channels in the vascular system of spontaneously hypertensive rats.…”
Section: Discussionsupporting
confidence: 73%